Echinococcus granulosus Infection Results in an Increase in Eisenbergiella and Parabacteroides Genera in the Gut of Mice - Bao, Jianling; Zheng, Huajun; Wang, Yuezhu; Zheng, Xueting; He, Li; Qi, Wenjing; Wang, Tian; Guo, Baoping; Guo, Gang; Zhang, Zhaoxia; Zhang, Wenbao; Li, Jun; et al. (Frontiers in Microbiology, 2018)
Cystic echinococcosis (CE) is a chronic infectious disease caused by Echinococcus granulosus. To confirm whether the infection impacts on the gut microbiota, we established a mouse model of E. granulosus infection in this study whereby BALB/c mice were infected with micro-cysts of E. granulosus. After 4 months of infection, fecal samples were collected for high-throughput sequencing of the hypervariable regions of the 16S rRNA gene. Sequence analysis revealed a total of 13,353 operational taxonomic units (OTUs) with only 40.6% of the OTUs having genera reference information and 101 of the OTUs were significantly increased in infected mice. Bioinformatics analysis showed that the common core microbiota were not significantly changed at family level. However, two genera (Eisenbergiella and Parabacteroides) were enriched in the infected mice (PAMOV A < 0.05) at genus level. Functional analysis indicated that seven pathways were altered in the E. granulosus Infection Group compared with the Uninfected Group. Spearman correlation analysis showed strong correlations of IgG, IgG1 and IgG2a with nine major genera. E. granulosus cyst infection may change the gut microbiota which may be associated with metabolic pathways.